Creating a "Ready-to-Use" AI Agent for Navigating Digital Platform to Enhance Collaborative Efficiency - Yiting, Qiu; SiYuan, Chen; Leong, Wai Yie (INTI International University, 2024)
The study aims to address the prevalent issue of navigation inefficiency within digital collaboration platforms, a critical factor affecting user productivity and satisfaction. This paper identifies research gaps and highlights the potential of multimodal AI Agents in revolutionising user experience in these platforms. Specifically, the development of a ready-to-use AI Agent was designed for the DingTalk platform, capable of guiding users through various digital functionalities via conversational interfaces. By leveraging recent advancements in large language models (LLMs) and the concept of "Model as a Service" (MaaS), the proposed AI solution seeks to overcome current navigation obstacles, thereby enhancing the sustainability and effectiveness of digital work ecosystems.